Performance and Durability Evaluation for Anode-Supported Solid Oxide Fuel Cell with Ce0.8Sm0.2O2−δ- SmBa0.5Sr0.5Co2O5+δ Composite Cathodes. (10th July 2019) - Lin, Tai-Nan; Kuo, Hong-Yi; Yeh, Chun-Yen; Kao, Wei-Xin; Cheng, Yung-Neng; Lee, Ruey-Yi
Abstract : We synthesize the SmBa0.5 Sr0.5 Co2 O5+δ (SBSC) powders by glycine nitrate combustion method and then design the composite cathodes by mixing with Sm0.2 Ce0.8 O2-δ (SDC) for thermal expansion mismatch concern. The cell exhibits good adhesion between layers to improve cell performance. The cell with yittria-stabilized zirconia (YSZ) electrolyte via cathode design of SDC | SDC-SBSC, is operated from 600 to 800 °C. The power densities for operation potential 0.7 V shows the acceptable value of 498 mWcm -2 at 800 °C. To evaluate the durability, it is operated under fixed current density over thousand hours. A slight degradation in the activation region can be observed at the initial stage. The degradation rate is estimated at less than 0.5 %/khr after activation with current loading. The operational conditions with lower current loading and higher operation potential are the solution to prolong the cell life time. Further demonstration for IT-SOFC cell product shall be executed.